2017
DOI: 10.3892/or.2017.5491
|View full text |Cite
|
Sign up to set email alerts
|

Co-treatment of breast cancer cells with pharmacologic doses of 2-deoxy-D-glucose and metformin: Starving tumors

Abstract: A characteristic of tumor cells is the increased aerobic glycolysis for energy production. Thus, inhibition of glycolysis represents a selective therapeutic option. It has been shown that glycolysis inhibitor 2-deoxy-D-glucose (2DG) induces apoptotic cell death in different tumor entities. In addition, the antitumor activity of the anti-diabetic drug metformin has been demonstrated. In the present study, we aimed to ascertain whether the combination of pharmacologic doses of 2DG with metformin increases the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
2
25
0
1
Order By: Relevance
“…Such INV showed upregulation of glucose uptake, and were effectively targeted using a glycolysis inhibitor, 2-DG. Several earlier studies have shown the ability of 2-DG to block cancer growth (12)(13)(14)(15)(47)(48). However, many of the clinical trials using 2-DG were discontinued due to the adverse side effects caused by the high doses of 2-DG (47,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such INV showed upregulation of glucose uptake, and were effectively targeted using a glycolysis inhibitor, 2-DG. Several earlier studies have shown the ability of 2-DG to block cancer growth (12)(13)(14)(15)(47)(48). However, many of the clinical trials using 2-DG were discontinued due to the adverse side effects caused by the high doses of 2-DG (47,49).…”
Section: Discussionmentioning
confidence: 99%
“…2-deoxy-D-glucose (2-DG), a D-glucose mimetic, inhibits glycolysis due to formation and intracellular accumulation of 2-deoxy-D-glucose-6-hosphate, inhibiting the function of hexokinase and glucose-6-phosphate isomerase (10)(11). 2-DG has a potential application as an adjuvant for improving cancer therapy, as it was to be able to reduce cancer cell viability (12)(13)(14)(15), and also assessed in several clinical studies as an anticancer agent (16)(17)(18). However, clinical use of 2-DG still has been carefully studied because of its side effects (14,19).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, glutamine deprivation sensitizes the resistant cells to BAY-876 inhibition. This synergism between glycolysis inhibitors combined with OXPHOS inhibition suggests a strong rationale using two or more drugs targeting different metabolic pathways to achieve superior therapeutic benefits for TNBC treatment 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…We rst con rmed that treatment of cells with 0.3 or 1 mM 2-DG for 16 h reduced lactate production by SUM149, MDA-MB-231, and HCC1937 cell lines (Supplemental Figure 8), suggesting that low concentration of 2-DG was su cient to reduce glycolysis. Inhibition of glycolysis is known to reduce cell viability (12)(13)(14)(15). Thus, we next investigated the sensitivity of SUM149, MDA-MB-231, or HCC1937 to same concentrations of 2-DG ( Figure 6A-C).…”
Section: Glycolysis Inhibitor Diminished Bc Invasionmentioning
confidence: 99%
“…2-deoxy-D-glucose (2-DG), a D-glucose mimetic, inhibits glycolysis due to formation and intracellular accumulation of 2-deoxy-D-glucose-6-phosphate, inhibiting the function of hexokinase and glucose-6-phosphate isomerase (10)(11). 2-DG has a potential application as an adjuvant for improving cancer therapy, as it was to be able to reduce cancer cell viability (12)(13)(14)(15) and has also been assessed in several clinical studies as an anticancer agent (16)(17)(18). However, clinical use of 2-DG still has been carefully studied because of its side effects (14,19).…”
mentioning
confidence: 99%